Manfaat dan Kendala Penerapan Tutor Sebaya untuk Siswa Kelas IV Sekolah Dasar Lentera Harapan Mamit - Ashiong Parhehean Munthe; Henny Pradiastuti Naibaho (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
Peer tutoring is a learning process that involves students who have high abilities to provide assistance and tutoring to students with lower abilities. There are benefits and constraints faced during the implementation of peer tutoring. This study aims to describe the benefits and constraints of the implementation of peer tutoring in fourth grade through the use of stacked short-division material. The research method used is descriptive qualitative research. The data obtained will be processed and described extensively and increasingly detailed, so that the reader will be able to comprehend the data descriptions. This research was conducted at Lentera Harapan Mamit School, Papua. The benefits of its implementation are students can express their learning difficulties directly to the tutor, students style understand the learning materials more easily because it uses the same language among fellow students. Peer tutoring also gives opportunities for students to grow together. The constraints faced are the difficulty in determining a more qualified tutor and in managing the time well because of many steps that must be applied. Preferably, while implementing peer tutoring, there should be a consideration on the selection of tutors by looking at the result of the student exercise periodically and using a timer to remind each step of the way.